Slime - Walliams, David 1971- (HarperCollins Children's Books, 2020)
Welcome to the Isle of Mulch. This little island is home to a large number of horrible grown-ups. The school, the local park, the toy shop and even the island's ice-cream van are all run by awful adults who like nothing more than making children miserable. And the island is owned by the most awful one of all, Aunt Greta Greed! Something needs to be done about them. But who could be brave enough? Meet Ned, an extraordinary boy with a special power. SLIMEPOWER!